Factorial design analysis of Zn(II) ions adsorption on thermally treated rice husk - Ong, Keat Khim; Ahmad Tarmizi, Ahmad Farhan; Wan Yunus, Wan Md Zin; Ahmad Zaidi, Ahmad Mujahid; Jabit, Mohd Lip; Fitrianto, Anwar; Safidin, K. M.; Abdul Rauf, Ummul Fahri; Che Ros, Fadhlina; Hussin, Abdul Ghapor; Ahmad @ Ayob, Mansor (Canadian Center of Science and Education, 2016)
Adsorption of Zn(II) ions from aqueous solutions by thermally treated rice husk was investigated using factorial experimental design to study effects of heating temperature and period of rice husk, pH, initial Zn(II) ion concentration, adsorption temperature and contact time, and adsorbent dosage. Main and interaction effects of these factors were analyzed using statistical techniques and the results were analyzed statistically using the Student’s t-analysis and analysis of variance which were used to determine significant factors that affect the percentage removal of Zn(II). These significant factors were heating temperature of rice husk, pH, initial metal concentration, contact time, and adsorbent dosage. The interaction between two different effects also affects the percentage removal of Zn(II) ions. These include the interactions between heating temperature of rice husk and initial metal concentration, pH and initial metal concentration, and pH and the adsorbent dosage.